Monitoring Of Mammals In The Territory Of The National Nature Park "Southern Ustyurt" (Texas Journal of Multidisciplinary Studies, 2025)
This article presents data on autumn monitoring of mammals distributed in the territory of the "Southern Ustyurt" National Nature Park in 2021-2024. Research work was carried out on the basis of generally accepted bioecological methods in the vicinity of Lake Sarykamysh, in the Kulan-Takyr, KaplanKyr, and Asseke-Audan depressions of Southern Ustyurt. As a result of the research, 14 species of mammals were identified. Eight of them are species listed in the Red Book of Uzbekistan